Psychological contracts and organizational commitment: The positive impact of relational contracts on call center operators - Stefania Fantinelli; Teresa Galanti; Gloria Guidetti; Federica Conserva; Veronica Giffi; Michela Cortini; Teresa Di Fiore (Administrative Sciences, 2023)
With the increasing complexity and dynamism of the modern work experience, the importance of the psychological contract has become increasingly clear. Organizations and researchers alike have recognized the implications of this contract for employee performance, satisfaction and well-being. However, certain work contexts can increase psychosocial risks, making it crucial to investigate the individual and contextual characteristics that can promote well-being and mitigate risks. In this study, we examined the impact of psychological contract types and task repetitiveness on organizational commitment among call center employees. By conducting a cross-sectional study involving 201 call center employees working in-person and administering an ad hoc questionnaire, we aimed to enrich the scientific literature on the psychological contract and its implications for the call center work environment. Our findings revealed that a transactional psychological contract has a negative impact on affective and normative commitment, potentially undermining employees' sense of obligation and responsibility towards these organizations. To promote healthy work relationships and well-being among call center employees, we suggest the importance of a relational psychological contract. By highlighting the role of psychological contract types in organizational commitment, our study offers valuable insights for both researchers and practitioners.
Keywords: 350; call center; commitment; exhausting work environment; healthy relationships; psychological contracts; relational capital